2021
DOI: 10.1128/aac.02605-20
|View full text |Cite
|
Sign up to set email alerts
|

Enisamium Reduces Influenza Virus Shedding and Improves Patient Recovery by Inhibiting Viral RNA Polymerase Activity

Abstract: Infections with respiratory viruses constitute a huge burden on our health and economy. Antivirals against some respiratory viruses are available, but further options are urgently needed. Enisamium iodide (laboratory code FAV00A, trade name Amizon®) is an antiviral marketed in countries of the Commonwealth of Independent States for the treatment of viral respiratory infections, but its clinical efficacy and mode of action are not well understood. Here, we investigated the efficacy of enisamium in patients aged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Previous experiments showed that enisamium ( Figure 1 A) can efficiently inhibit influenza virus replication in normal human bronchial epithelial (NHBE) cultures and A549 cells, and to a lesser extent in Caco-2 cells [ 13 ]. Previous experiments have also demonstrated that enisamium is not cytotoxic to these cells [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous experiments showed that enisamium ( Figure 1 A) can efficiently inhibit influenza virus replication in normal human bronchial epithelial (NHBE) cultures and A549 cells, and to a lesser extent in Caco-2 cells [ 13 ]. Previous experiments have also demonstrated that enisamium is not cytotoxic to these cells [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were infected with SARS-CoV-2 at multiplicity of infection 0.01 for 1 h, and compound reapplied following virus removal. At 48 h post infection, the cytopathic effect was recorded by examination of the infected cultures by light microscopy and supernatant collected to quantify virus RNA by RT-qPCR as described previously, using nsp12-specific primers 5′-GTGARATGGTCATGTGTGGCGG-3′ and 5′-CARATGTTAAASACACTATTAGCATA-3′ [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Cells were fixed with acetone/methanol (40:60) and immunostained using a SARS-CoV-2 nucleoprotein monoclonal antibody (1:500, Sinobiological, Cat #40143-R019-100 µL).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations